PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR SISWA ( Studi pada Muatan Pelajaran IPA Kelas V SD Negeri 9 Lahat ) - Sugiono Sugiono (DIADIK, 2020)
This study aims to describe the application of the type of picture and picture cooperative   learning   models   to   increase   student   responsibility   and   learning achievement. This research uses the Classroom Action Research (CAR) method which is carried out in three cycles with four stages consisting of planning, implementation, observation, and reflection. This research also uses quasi experiment. The subject of the study was the second semester of VB grade students in the 2019/2020 school year at SD Negeri 9 Lahat, totaling 25 students. Whereas the quasi-experiments were VA and VC grade students, each of which numbered 25 students. Data collection instruments in this study used  observation  sheets  and  tests.  Analysis  of research  data  using  statistical averages (mean), percentages and t-test.